Strategies to achieve economic sustainability in a city with limited space (Case Study Cimahi Municipality) - Pingkan Ketzia Tulangow (Journal of Sustainable Engineering: Proceedings Series, 2019)
New Urban Agenda (NUA) is the agreement of 197 countries in UN Habitat III Conference. NUA represents a shared vision for a better and more sustainable future. NUA has 3 principles, one of them ensure sustainable and inclusive urban economies. Cimahi Municipality is has many limitation to build the city physically. Cimahi in 2017 has 601.099 people (BPS, 2018), while the area of city only 40.20 km2 and the density 14.953 people/km2. In physical development, Cimahi limited by Kawasan Bandung Utara regulation for building coverage ratio and also by Kawasan Keselamatan Operasi Bandar Udara Husein Sastranegara regulation for floor area ratio. This research would formulate strategy to achieve the economic sustainability. SWOT analysis and 5C strategy are the method to formulate the strategy. Creative industry is the economic sector that should be develops base one condition that Cimahi had the people with good quality, but had a limited space to build the new production place and had limited natural resource. Based on SWOT analysis there are 12 strategies to develop creative economic. The core strategy is to encourage people to become entrepreneur